Information mobility: from the library to the living room - Lara-Navarra, Pablo (Anuario ThinkEPI, 2009)
Mobility projects are focusing much of the innovation efforts for those working with information technologies. The three main elements that allow mobility (technology, software and information), showing the main trends and developments in the market.
Keywords: Information mobility; Information technologies; Media centers; Interoperability; Multiplatform content.